An Updated Review on Oxaliplatin Induced Peripheral Neuropathy - Anudeepika, Meesala (International Journal of Pharmaceutical & Biological Archive, 2023)
Peripheral neuropathy (PN) is a common condition that affects roughly 5% of the general population after the age of 50. PN can be caused by a variety of factors, including chemotherapy medicines, heredity, diabetes, alcohol, vitamin deficiencies, and gluten sensitivity. This article concentrates on oxaliplatin-induced PN in this review. Oxaliplatin (OHP) is a significant component of colorectal, gastric, and pancreatic cancer chemotherapy, yet it frequently causes PN as a dose-limiting factor. OHP-induced neurotoxicity manifests as acute neuropathic symptoms exacerbated by cold exposure as well as chronic neuropathy that develops after several treatment cycles. Despite the fact that many basic and clinical researchers have investigated anticancer drug-induced PN, the mechanism remains unresolved. According to clinical data, more than 65% of patients reduce or discontinue OHP due to this adverse effect, reducing their chances of survival. This article reviews in detail aspects of OHP-induced PN such as risk factors, types of neuropathy, various animal models, mechanisms of OHP-induced peripheral neuropathy, pathophysiology, diagnosis, and management and additionally determines future research directions.